PENGARUH EMOSI POSITIF DAN PROMOSI PENJUALAN TERHADAP MINAT BELI (STUDI PADA COFFEE SHOP EPIDEMI JOMBANG) - Prada, Bagas Maulana Pasha Aditya; Kurniawan, Indra (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
This study seeks to ascertain the impact of favorable emotions and sales promotions on consumer purchasing intentions. This study used quantitative research as many as 96 respondents in Jombang Regency who will visit or have visited Coffee Shop Epidemic. This research employed a questionnaire-based data collection approach, disseminated through purposive sampling methods. Data analysis involved employing various statistical techniques, including multiple linear regression analysis, validity and reliability assessments, F-tests, t-tests, and correlation coefficient and determination assessments utilizing SPSS 25 software. The results of this study suggest that positive emotions significantly influence the likelihood of making a purchase. Moreover, sales promotions wield a noteworthy impact on purchasing intent as well. Furthermore, there exists a concurrent effect of favorable emotions and sales promotions on purchasing intent.